WDR36 Regulates Trophectoderm Differentiation During Human Preimplantation Embryonic Development Through Glycolytic Metabolism - Shiyu An; Shuyue Hou; Feifei Xu; Huanyu Yan; Wenyi Zhang; Jinfeng Xiang; Haoran Chen; Hanwen Zhang; Lingling Dong; Xiaobin Sun; Ran Huo; Yun Chen; et al. (Advanced Science)
Abstract Mammalian pre‐implantation development is a complex process involving sophisticated regulatory dynamics. WD repeat domain 36 (WDR36) is known to play a critical role in mouse early embryonic development, but its regulatory function in human embryogenesis is still elusive due to limited access to human embryos. The human pluripotent stem cell‐derived blastocyst‐like structure, termed a blastoid, offers an alternative means to study human development in a dish. In this study, after verifying that WDR36 inhibition disrupted polarization in mouse early embryos, it is further demonstrated that WDR36 interference can block human blastoid formation, dominantly hindering the trophectoderm lineage commitment. Both transcriptomics and targeted metabolomics analyses revealed that WDR36 interference downregulated glucose metabolism. WDR36 can interact with glycolytic metabolic protein lactate dehydrogenase A (LDHA), thereby positively regulating glycolysis during the late stage of human blastoid formation. Taken together, the study has established a mechanistic connection between WDR36, glucose metabolism, and cell fate determination during early embryonic lineage commitment, which may provide potential insights into novel therapeutic targets for early adverse pregnancy interventions.